Impedance modeling for polymer electrolyte membrane fuel cells by combining the transient two-phase fuel cell and equivalent electric circuit models. (15th January 2022) - Lee, Jiseung; Salihi, Hassan; Lee, Jaeseung; Ju, Hyunchul
Abstract: Proton exchange membrane fuel cell (PEMFC) are actively replacing fossil fuel-based energy systems in commercial applications. Evaluation of cell performance and degradation is critical and usually performed by analyzing the polarization curve and/or Nyquist plot. The polarization test provides an insight into the entire cell, whereas electrochemical impedance spectroscopy (EIS) is used to obtain the Nyquist plot that facilitates the assessment of individual voltage losses occurring in the inner components of a PEMFC. This paper highlights the degradation assessment of PEMFCs using a coupled one-dimensional (1-D) two-phase PEMFC model and Randles-TLM equivalent circuit model. The 1-D model includes a micro-scale catalyst layer (CL) model to more accurately assess electrochemical catalyst activity and mass transport inside the agglomerated porous structure of CL. This model is utilized to estimate key input parameters for various PEMFC operating conditions and degradation scenarios, which are then applied to the equivalent circuit model. The coupled model simulations successfully reproduce both experimental polarization curves and Nyquist plots for various PEMFC conditions. This study enhances the understanding of underlying physical phenomena occurring during long-term PEMFC operations. Highlights: EIS data of flooding and dehydration degradations have been numerically studied. Good agreement between simulated and measured impedance has been achieved. In flooding degradation, a relatively high degree of concentration overpotential and diffusion resistance was observed. Higher ohmic resistance for the dehydration case can be observed as a longer straight line in the high frequency region. Higher values of constant phase elements were predicted for all the degradation cases compared to respective pristine cases.